The Role of β-Catenin in Th1 Immune Response against Tuberculosis and Profiles of Expression in Patients with Pulmonary Tuberculosis - Kunlong Xiong; Jinxia Niu; Ruijuan Zheng; Zhonghua Liu; Yanzheng Song; Lin Wang; Changtai Zhu; Lin Fan (Journal of Immunology Research)
β-Catenin is a key molecule of canonical Wnt/β-catenin pathway. Its roles and expression profiles in T cells of tuberculosis (TB) remain unclear. The aim of this study was to explore the role of β-catenin in CD4+ T cells and its expression characteristics in patients with pulmonary tuberculosis (PTB). In this study, CD4+ T cell-specific β-catenin conditional knockout mice (β-CAT-cKO mice) were aerosol infected with Mycobacteria tuberculosis (Mtb) H37RV with wild-type mice as controls. Four weeks after infection, the mRNA expression of IFN-γ, TNF-α, and TCF-7 in the lungs of mice was measured. CD4, CD8, β-catenin, IFN-γ, and TNF-α in mononuclear cells from the lungs and spleens were measured by flow cytometry, and the pathological changes of lungs were also observed. Patients with PTB were enrolled, with blood samples collected and PBMCs isolated. The expressions of β-catenin, IFN-γ, TNF-α, and PD-1 in CD4+ and CD8+ T cells were measured by flow cytometry. Results showed a decreased frequency of and reduced IFN-γ/TNF-α mRNA expression and secretion by CD4+ T cells in the lungs of infected β-CAT-cKO mice compared with infected wild-type controls, and only slightly more inflammatory changes were observed in the lungs. β-catenin expressions in CD4+ and CD8+ T cells were significantly decreased in blood cells of patients with severe PTB compared with those in mild PTB. The stimulation of peripheral blood mononuclear cells (PBMCs) with lithium chloride (LiCl), a stimulant of β-catenin, resulted in the increase in CD4+ T cell frequency, as well as their secretion of IFN-γ and TNF-α. β-Catenin demonstrated a moderately positive correlation with PD-1 in CD4+ T cells. β-Catenin along with PD-1 and IFN-γ in CD4+ T cells had a high correlation with those in CD8+ T cells. In conclusion, β-catenin may be involved in the regulation of Th1 response and CD4+ T cell frequency in TB.